ABORSI DALAM PANDANGAN HUKUM ISLAM KAITANNYA DENGAN DIBOLEHKANNYA MENURUT PP NOMOR 61 TAHUN 2014 TENTANG REPRODUKSI - Nofiardi, Nofiardi (Alhurriyah, 2015)
A fetus life in Islamic law is an honorable life and it is prohibited to do the persecution to the fetus, even if it is done by the parents, including by the mother who conceives him in hard and rough situations. Therefore it is very interesting to discuss about abortion in Islamic law point of view in relation to Government Regulation No. 61/2014 About reproduction, either the abortion is done before or after blowing the spirit.